Competing Compatibility Standards and Network Externalities in the PC Software Market - Gandal, Neil (The Review of Economics and Statistics, 1995)
This paper is an empirical study of the value of four file compatibility standards for transferring data in the personal computer software market. The results are that only the LOTUS file compatibility standard is significant in explaining price variations and it is significant in both the spreadsheet and database management system markets. This supports the hypothesis that the personal computer software market exhibits complementary network externalities. Copyright 1995 by MIT Press.